Distributional consequences of direct foreign investment - Frank, Robert H.; Freeman, Richard T. (New York : Academic Press, 1978)
The book seek to evaluate the merit of the fundamental economic questions that have been raised in economic debate on the net effect of overseas investment of United States through multinational corporations.
Bibliography: p. [153]-157.
usc 18/09/18
Loans
Keywords: Investments, American; Investments, Foreign, and employment; Investments, Foreign, and employment--Mathematical models; United States